Ring‐Opening Polymerisation of Low‐Strain Nickelocenophanes: Synthesis and Magnetic Properties of Polynickelocenes with Carbon and Silicon Main Chain Spacers. Issue 4 (26th November 2018) - Hailes, Rebekah L. N.; Musgrave, Rebecca A.; Kilpatrick, Alexander F. R.; Russell, Andrew D.; Whittell, George R.; O'Hare, Dermot; Manners, Ian
Abstract: Polymetallocenes based on ferrocene, and to a lesser extent cobaltocene, have been well‐studied, whereas analogous systems based on nickelocene are virtually unexplored. It has been previously shown that poly(nickelocenylpropylene) [Ni(η 5 ‐C5 H4 )2 (CH2 )3 ] n is formed as a mixture of cyclic (6 x ) and linear (7 ) components by the reversible ring‐opening polymerisation (ROP) of tricarba[3]nickelocenophane [Ni(η 5 ‐C5 H4 )2 (CH2 )3 ] (5 ). Herein the generality of this approach to main‐chain polynickelocenes is demonstrated and the ROP of tetracarba[4]nickelocenophane [Ni(η 5 ‐C5 H4 )2 (CH2 )4 ] (8 ), and disila[2]nickelocenophane [Ni(η 5 ‐C5 H4 )2 (SiMe2 )2 ] (12 ) is described, to yield predominantly insoluble homopolymers poly(nickelocenylbutylene) [Ni(η 5 ‐C5 H4 )2 (CH2 )4 ] n (13 ) and poly(tetramethyldisilylnickelocene) [Ni(η 5 ‐C5 H4 )2 (SiMe2 )2 ] n (14 ), respectively. The ROP of8 and12 was also found to be reversible at elevated temperature. To access soluble high molar mass materials, copolymerisations of5, 8, and12 were performed. Superconducting quantum interference device (SQUID) magnetometry measurements of13 and14 indicated that these homopolymers behave as simple paramagnets at temperatures greater than 50 K, with significant antiferromagnetic coupling that is notably larger in carbon‐bridged6 x /7 and13 compared to the disilyl‐bridged14 . However, the behaviour of these polynickelocenes deviates substantially from the Curie–Weiss law at low temperatures due to considerable zero‐field splitting. Abstract : Ring‐opening polymerisation (ROP) of tetracarba[4]nickelocenophane and disila[2]nickelocenophane to yield predominantly insoluble homopolymers, and the reversible nature of this ROP at elevated temperature is described. SQUID magnetometry indicated that the homopolymeric materials behave as simple paramagnets at T > 50 K, with significant antiferromagnetic coupling, but deviate substantially from the Curie–Weiss law at low temperatures.